Revisiting the Anterolateral Ligament of the Knee - Kosy, Jonathan D.; Mandalia, Vipul I. (The Journal of Knee Surgery, 2016)
Recent research has suggested that the anterolateral ligament (ALL) of the knee may have an important role in preventing persistent rotatory instability following anterior cruciate ligament (ACL) reconstruction.For this review, we performed a thorough literature search and identified the significant steps in the improvement of our understanding. This has progressed from historical reports to accurate characterization of the attachments and dimensions of the ALL through anatomical and histological studies. Alongside this, biomechanical data have demonstrated the role of this structure throughout the range of movement of the knee. Furthermore, the appearance of the ALL on magnetic resonance imaging has been comprehensibly described and radiological markers have been defined as a basis for suggested reconstructive procedures using fluoroscopy.We present a comprehensive review of the evolution of our understanding about this structure. Key advances in our understanding of the dimensions and attachments will guide research into reconstructive options. Further work is needed to determine the biomechanical and clinical outcome of extra-articular reconstruction of the ALL alongside ACL reconstruction.
Keywords: anterolateral ligament; anterior cruciate ligament reconstruction; knee anatomy; knee biomechanics